Wastewater Gardens as Alternative to Treat Wastewater: Five Wastewater Garden Experiences in Barra Honda and La Vigía de Nicoya, Guanacaste, Costa Rica - Cubillo Paniagua, María Fernanda (2017)
The present work seeks to promote wastewater gardens as an efficient system of low-cost treatment for sewage water. This intention came up from the benefits obtained with the implementation of five of these methods as part of a project conducted in Barra Honda and La Vigía de Nicoya, Guanacaste, Costa Rica. In fact, the project “Improvement in the treatment of sewage water through wastewater gardens” was implemented with the purpose of informing individuals, institutions and the country about these systems, and raising awareness of and interest in initiatives that encourage research efforts, awareness raising and development of these methods, and thus, to continue advancing in the articulation of efforts from the institutional and community level in order to improve the public health and the natural ecosystems. Zuñiga (2015) says that “due to little attention and importance given to the treatment of sewage water in Costa Rica in the regulatory field, in its practice and in its supervision, this process remains the most important challenge in order to manage the pollution risk of water bodies.”